Keputusan Pembelian Memediasi Fasilitas dan Persepsi Harga Terhadap Minat Beli Ulang - Devi Putri Maharani; Prabowo, Heri; Nastiti , Prianka Ratri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of facilities and price perception on repurchase intention through purchase decision as mediating variables on customers Alfamart Ampelgading branch, Pemalang Regency. In order to retain consumers and increase sales to be stable, it is necessary to pay attention to store facilities whether the price set is a affordable by the community, so that it will increase purchasing decision in consumers. This study uses a quantitative approach by distributing questionnaires to 96 respondents, using a purposive sampling technique. Data analysis was carried out using SmartPLS 4 in 2025 with a measurement model (inner model) and a structural model (outer model). The results of this study indicate that facilities and price perceptions have a positive and significant effect on purchasing decisions, facilities and price perceptions have a positive and significant effect on repurchase intentions, purchase decisions have a positive and significant effect on repurchase intentions, fasilities and price perceptions have a positive and significant effect on repurchase intentions with purchase decisions as a mediating variables. These findings provide partical implications for companies, especially in maintaining facilities, meeting consumer needs, and maintining price consistency with quality to encourage repeat purchases after previously purchasing a product.